2023
DOI: 10.3390/tropicalmed8030180
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Case Detection Strategy for Malaria Control and Elimination: A 12 Year Systematic Review and Meta-Analysis from 25 Malaria-Endemic Countries

Abstract: Reactive case detection (RACD) is the screening of household members and neighbors of index cases reported in passive surveillance. This strategy seeks asymptomatic infections and provides treatment to break transmission without testing or treating the entire population. This review discusses and highlights RACD as a recommended strategy for the detection and elimination of asymptomatic malaria as it pertains in different countries. Relevant studies published between January 2010 and September 2022 were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In contexts with low or very low malaria transmission, reactive case detection and treatment and reactive indoor residual spraying have been shown to be pertinent and effective, as has targeted mass drug administration [ 39 , 53 – 55 ]. Looking at our results, these three strategies, if implemented in SGO, should consider both the area around the targeted population’s homes and the places these people have visited when the vector is present (e.g., slash-and-burn fields, medium to high vector density areas).…”
Section: Discussionmentioning
confidence: 99%
“…In contexts with low or very low malaria transmission, reactive case detection and treatment and reactive indoor residual spraying have been shown to be pertinent and effective, as has targeted mass drug administration [ 39 , 53 – 55 ]. Looking at our results, these three strategies, if implemented in SGO, should consider both the area around the targeted population’s homes and the places these people have visited when the vector is present (e.g., slash-and-burn fields, medium to high vector density areas).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting on RACD used a number of protocols to assess its effectiveness. Despite this, RACD was generally implemented in lower endemic settings [ 11 ]. According to the WHO, an annual parasite prevalence of 1–10% is considered low and ≥ 35% as high [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, an annual parasite prevalence of 1–10% is considered low and ≥ 35% as high [ 12 ]. Aidoo et al [ 11 ], in a systematic review of 55 published studies that reported on RACD from 25 countries, had no record of its implementation in Ghana. Malaria elimination is often first achieved in parts of the areas within a country and prevention of re-establishment started at the subnational level while countries are working on full interruption of transmission in all their regions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…mosquitoes (3). The World Malaria Report 2022 states that there will be an estimated 247 million malaria cases in 84 malaria-endemic countries in 2021 (4). Data from the Ministry of Health of the Republic of Indonesia in 2021 indicated that there were 304,607 malaria cases in Indonesia (5).…”
Section: Introductionmentioning
confidence: 99%